Diversity of physical properties of bacterial extracellular membrane vesicles revealed through atomic force microscopy phase imaging. Issue 14 (31st March 2020) - Kikuchi, Yousuke; Obana, Nozomu; Toyofuku, Masanori; Kodera, Noriyuki; Soma, Takamitsu; Ando, Toshio; Fukumori, Yoshihiro; Nomura, Nobuhiko; Taoka, Azuma
Abstract : This study provides a new methodology using phase imaging for quantitative single-vesicle physical characterization of extracellular bacterial membrane vesicles. Abstract : Bacteria release nanometer-scale extracellular membrane vesicles (MVs) to mediate a variety of biological processes. We analyzed individual MVs under physiological conditions by phase imaging of high-speed atomic force microscopy to assess the physiological heterogeneity of MVs isolated from bacterial cultures. Phase imaging makes it possible to map the physical properties of an individual, fragile MV in an isolated MV population containing a broad variety of vesicle diameters, from 20 to 150 nm. We also developed a method for quantitatively comparing the physical properties of MVs among samples. This allowed for the comparison of the physical properties of MVs isolated from different bacterial species. We compared bacterial MVs isolated from four bacterial species and artificially synthesized liposomes. We demonstrate that each bacterial species generates physically heterogeneous types of MVs, unlike the physical homogeneity displayed by liposomes. These results indicate that the physical heterogeneity of bacterial MVs is mainly caused by compositional differences mediated through biological phenomena and could be unique to each species. We provide a new methodology using phase imaging that would pave the way for single-vesicle analysis of extracellular vesicles of a broad size range.